Engine displacement modularity for enhancing automotive s.i. engines efficiency at part load. (15th September 2016) - Millo, F.; Mirzaeian, M.; Luisi, S.; Doria, V.; Stroppiana, A.
Abstract: Cylinder deactivation is a well-known and effective technology to improve spark ignition engines' efficiency at part load, thanks to its capability of significantly reducing pumping losses, by switching off a fraction of the cylinders at part load, while operating the active cylinders at higher loads and therefore with higher efficiencies. This technology can be utilized as an alternative to, or in combination with, other efficiency improving measures such as engine downsizing and Variable Valve Actuation (VVA). It is worth mentioning however that the implementation of a cylinder deactivation strategy generally requires intake and exhaust valve deactivation in deactivated cylinders, so to minimize pumping losses thanks to the "gas spring" behavior of the trapped charge. In this paper the effects and possible benefits of cylinder deactivation on a four cylinder turbocharged downsized gasoline engine equipped with MultiAir VVA system were experimentally investigated, aiming to obtain further reductions of pumping losses beyond those achievable through normally adopted Early Intake Valve Closure (EIVC) strategies. Moreover, since the MultiAir VVA system does not allow exhaust valve deactivation, an innovative strategy was developed, exploiting internal Exhaust Gas Recirculation (iEGR) in the inactive cylinders in order to minimize their pumping losses. This innovative cylinder deactivation technique was demonstrated to be effective in the low speed and low load operating region of the engine map, leading to an impressive 30% reduction of pumping losses compared to the EIVC unthrottled load control.